2012
DOI: 10.1108/00220411211277055
|View full text |Cite
|
Sign up to set email alerts
|

Community information as boundary object: police responsibility for abuse survivors

Abstract: Purpose -Working toward a symbolic interactionist understanding of information provision by multiple agencies responding to crisis situations, in this paper the authors aim to examine mandated information provision on the part of US law enforcement to survivors of intimate partner violence. Design/methodology/approach -The authors conducted a detailed content analysis of 1,793 documents supplied by local law enforcement agencies from over 700 cities from all 50 US states. Documents were coded within a framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Godbold (2012) identified an element of the BO, its useful vagueness, to show how personal narratives on online discussion groups became recognizable and vague enough to fit in a general way with the situations of discussion group readers. Westbrook and Finn (2012) showed that this vagueness is not always helpful. They found that tensions may arise as a result of the distinct priorities and perspectives that each member of a broad network of community partners brings to the problem of intimate partner violence (IPV).…”
Section: Information Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Godbold (2012) identified an element of the BO, its useful vagueness, to show how personal narratives on online discussion groups became recognizable and vague enough to fit in a general way with the situations of discussion group readers. Westbrook and Finn (2012) showed that this vagueness is not always helpful. They found that tensions may arise as a result of the distinct priorities and perspectives that each member of a broad network of community partners brings to the problem of intimate partner violence (IPV).…”
Section: Information Practicesmentioning
confidence: 99%
“…BOs can be identified in diverse 'informational' situation within which their vagueness turns to an asset. The line between being vague enough and too indefinite is fine and as, for instance, the example of Westbrook and Finn (2012) shows, BOs can fail. Even if the BOs are fallible and in a constant process of (re-)making, the review shows that the recent theoretical shift in information behavior research towards the notion of information practices has increased the relevance of the notion and its usefulness as an analytical lens for explicating continuities and discontinuities of collaborative information activities.…”
Section: Information Practicesmentioning
confidence: 99%
See 3 more Smart Citations